Prevalence and Predictors of Bladder Outlet Obstruction in Women With Chronic Urinary Symptoms and a History of Urethral Sling Surgery. Issue 2 (17th November 2022) - Ross, James; Avvakoumova, Lidia; Yassein, Alaya; Payne, Magdalene; Maciejewski, Conrad; Mallick, Ranjeeta; Breau, Rodney H.; Vigil, Humberto; Hickling, Duane
Abstract : Purpose: The objective of this study is to review patients with chronic urinary symptoms and remote urethral sling surgery to determine the prevalence and predictors of obstruction. Materials and Methods: A single-center retrospective review was performed on patients referred with chronic lower urinary tract symptoms (>6 months) and a history of urethral sling surgery. Obstruction was identified by urodynamics using the Blaivas criteria or fluoroscopy. Clinical findings for patients with and without obstruction were compared. Logistic regression was applied to identify predictors of urodynamic obstruction. The need for sling revision and post-revision outcomes were evaluated. Results: In total 105 patients were included, median age 61 years (IQR 19), median time since sling surgery 5.0 years (IQR 8). Sixty percent (63/105) met the definition for obstruction. Patients with obstruction had higher mean detrusor pressure at maximum urinary flow rate (35 vs 19 cm H2 O) and lower maximum urinary flow rate (6.0 vs 14 mL/s; P < .05). A tight suburethral band and increased post-void residuals were significantly associated with urodynamic obstruction ( P < .05). Fifty-nine (59/105; 56%) patients underwent suburethral sling excision. The incidence of improvement in storage and voiding symptoms at 6 months was 43% and 87%, respectively. At 30 months post-excision, the probability of being incontinence-free was 56% (95% CI 41, 69) and the probability of being free from redo sling surgery was 75% (95% CI 55, 87). Conclusions: Obstruction is common in patients with chronic urinary symptoms and history of urethral sling surgery. Patients undergoing sling revision should be observed for persistent storage symptoms and recurrent incontinence.